Survey on farm tractor (John Deere) total cost in field FFB evacuation. A case study in Far East Holding Berhad / Mohd Zulazriey Zulkifly - Zulkifly, Mohd Zulazriey (Faculty of Plantation and Agrotechnology, 2019)
Estate Mechanization is becoming more important in overcoming labour shortage and enhancing labour productivity. That is more type of mechanization been used in plantation example is a Farm Tractor (FT) to easy the process evacuate the product from in-field to the mill. This study focuses on a survey the total cost in-field Fresh Fruit Bunches (FFB) evacuation. The study was conducted Far East Holding, Ladang Sungai Gayung, Pahang. The objective of this study is to study the total cost of FFB evacuation by tractor per year in the field, a factor that influences the total cost of FT per year and to study the effectiveness and efficiency of total cost toward the tractor operation. The FT used is John Deere 5715 model, 89hp. This study will be obtained by secondary data which is collected based on the real field of oil palm plantation. The data have been collected for the four years times period and more focusing on the total operating cost which is Fuel, lubricants, repair, maintenance and labour. Fixed cost like depreciation, tax and insurance not be calculated because this estate uses the old tractor. The higher total operating cost for the year 2017 is at February which is RM 6442 because the tractor was a breakdown and go to the workshop. Based on four years data analysis, it shown 2017 is the highest operating cost which is RM 52275 and 2016 is the lowest operating cost with RM 37518. Based on the data analyse it shown that more lifespan of the tractor, more expenses of total operating cost to be spent to maintain the FT in good condition and to running maximise to increase the profitability of the company.